Social justice : theories, issues, and movements - Capeheart, Loretta, 1963-; Milovanovic, Dragan, 1948- (Critical issues in crime and society., 2020)
"An eye for an eye, the balance of the scales - for centuries, these and other traditional concepts exemplified the public's perception of justice. Today, popular culture, including television shows like Law and Order, informs the public's vision. But do age-old symbols, portrayals in the media, and existing systems truly represent justice in all of its nuanced forms, or do we need to think beyond these notions? The second edition of Social Justice: Theories, Issues, and Movements responds to the need for a comprehensive introduction to these issues. Theories of social justice are presented in an accessible fashion to encourage engagement of students, activists, and scholars with these important lines of inquiry. Issues are analyzed utilizing various theories for furthering engagement in possibilities. Struggles for justice from legal to on the ground movements are presented for historical context and to inform the way forward"--